2014
DOI: 10.1007/s10047-014-0770-4
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of 17-mm St. Jude Medical Regent prosthetic valves in elder patients with small aortic annuli: comparison with 19-mm bioprosthetic valves

Abstract: This study was designed to compare the mid-term outcomes after aortic valve replacement (AVR) between 17-mm mechanical heart valves (MV) and 19-mm bioprosthetic valves (BV) in elderly patients with small aortic annuli. Between 2000 and 2011, 127 consecutive patients (mean age 79 years; 87 % female) underwent AVR for aortic valve stenosis with a small aortic annulus. 19-mm BV (n = 67) was implanted. When the 19-mm BV did not fit the annulus, 17-mm St. Jude Medical Regent prosthetic mechanical valve (n = 60) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Teshima et al [33] compared the midterm outcomes after aortic valve replacement (AVR) between 17-mm SJM mechanical heart valves (MV) and 19-mm bioprosthetic valves (BV) in elderly patients with small aortic annuli in elderly patient. They demonstrated that AVR using 17-mm MV in elder patients with small aortic annuli provided equivalent midterm clinical results to that with 19-mm BV.…”
Section: Artificial Valvementioning
confidence: 99%
“…Teshima et al [33] compared the midterm outcomes after aortic valve replacement (AVR) between 17-mm SJM mechanical heart valves (MV) and 19-mm bioprosthetic valves (BV) in elderly patients with small aortic annuli in elderly patient. They demonstrated that AVR using 17-mm MV in elder patients with small aortic annuli provided equivalent midterm clinical results to that with 19-mm BV.…”
Section: Artificial Valvementioning
confidence: 99%